An Analytical Assessment of Muhammad Iqbal's Framework of Ijtihad - Abdul Rahim, Adibah (National University Malaysia (UKM), 2014)
In the nineteenth and twentieth centuries, Muslim countries were occupied by Western powers that came across the local Muslim culture and traditions. The Muslim world at that time was thrown into great crisis caused by the conflict between conservatism and modernism. The conservatives became rigid in their outlook and approach. They concluded that the only way to save Islamic law and culture, and Muslim society in the conflict of the West was to stick to the past and guard the old establishment. This is called taqlid or blind imitation. Meanwhile, the modernists confined themselves to the imitation of the West, and argued for the adoption of Western civilization, so that Muslim could emerge as a progressive nation. While the conservatives stood for rigid adherence to fiqh, the modernists wanted to change the entire law in the light of Western codes of law. Iqbal argued that neither conservatism nor modernism were good. According to him, the conservatives’ approach was unrealistic because it rejects the ontological principle of change; i.e due to a process of continuous change of life, new situations arise and new problems occur. Meanwhile, the modernists’ approach is unrealistic because it has often ended up in the garb of westernization rather than modernization. Iqbal took a balance approach between conservatism and modernism whereby he acknowledged conservatives’ approach which firmly anchored in the Muslim heritage, and the modernists’ approach which tailored to meet the challenge of modern times to maintain the dynamic character of Islam. In his synthetic approach, Iqbal tried to reinterpret the whole development of Islamic thought through the principle of ijtihad, and stressed its dynamic element in it rather than static. For Iqbal, ijtihad was the only way to rescue Muslims from the stagnation of thought which had deprived them of religious, social, economic, educational, legal, and political ascendency in the world. This paper attempts at analyzing Iqbal’s constructive approach to the principle of ijtihad, and its significance to contemporary Islam.